Manajemen Pemasaran Budidaya Tanaman Hidroponik Pada Central Hydroponik Bengkulu - Puspita, Sinta Dian; Monique, Eska Prima; Effendi, Yanto; Nasution, Suswanti (Universitas Dehasen Bengkulu, 2024)
Macroeconomic changes in Indonesia have encouraged investors' interest in investing in business sectors that are not dominated by imported components. Profit potential and specific segment selection create competition between manufacturers and high standards of cooperation set by retailers. Manufacturers must be able to produce products that are high quality, uniform, clean, attractive, able to supply continuously according to demand and other requirements. Central Hydroponil Bengkulu is Sumardi's hydroponic plant cultivation and is cultivated on one hectare of land, located on Jalan Karbela RT 01, RW 01 Padang Jati Village. Referring to the full commercialization aspect that characterizes management's business, the success of this hydroponic business can be achieved if management's attention is not focused only on the production side, but also on the marketing side. Marketing at Central Hydroponics Bengkulu is done in several ways, including joining a community or association, selling directly to the market, selling directly from the garden, using social media, joining the marketplace.